Borrowing in The Novel The Hound of The Baskervilleand Its Translation - Sanditha, Agus Yuda Renanda; Sosiowati, I Gusti Ayu Gede (Humanis; Vol 24 No 2 (2020)DO - 10.24843/JH.2020.v24.i02.p03, 2020)
This study is aimed to find out the types of Borrowing that is used in translation of the novel The Hound of the Baskerville and the dominant type of borrowing in used. The data were taken from a novel entitled “The Hound of The Baskervilles” by Sir Arthur Conan Doyle and its translation in Indonesia by Dina Begum. This study used library method to collected the data from the novel. To analyse the data, this study usedqualitative method.  As for analysis of data presentation, this study used formal and in-formal method. The finding showed there are two type of borrowing used in the novelthey are Pure Borrowing and Naturalized Borrowing.The dominant type of borrowing is Naturalized Borrowing with 138data.